The discovery of a conjugate system of faults in the Wharton Basin intraplate deformation zone - Singh, Satish Chandra (2017)
The deformation at well-defined, narrow plate boundaries depends on the relative plate motion, but how the deformation takes place within a distributed plate boundary zone remains a conundrum. This was confirmed by the seismological analyses of the 2012 great Wharton Basin earthquakes [moment magnitude (Mw) 8.6], which suggested the rupture of several faults at high angles to one another. Using high-resolution bathymetry and seismic reflection data, we report the discovery of new N294°E-striking shear zones, oblique to the plate fabric. These shear zones are expressed by sets of normal faults striking at N335°E, defining the direction of the principal compressional stress in the region. Also, we have imaged left-lateral strike-slip faults along reactivated N7°E-oriented oceanic fracture zones. The shear zones and the reactivated fracture zones form a conjugate system of faults, which accommodate present-day intraplate deformation in the Wharton Basin.